The Evaluation Method of Flow and Temperature Field for a Subsea Cage-Type Choke Valve - Wujun Tong; Yingying Wang; Zeqing Lin; Dingwen Huang; Haibo Li; Xinzhong Li (Journal of Marine Science and Engineering, 2026)
As a critical regulating component in subsea Christmas tree systems, the cage-type choke valve governs the overall production efficiency and operational reliability of offshore oil and gas exploitation owing to its unique internal flow field characteristics. In accordance with the in situ operating conditions of the target oilfield, this paper performs a numerical simulation and systematic analysis on the flow field behaviors of a cage-type choke valve. Based on the fundamental theories of computational fluid dynamics (CFD), a three-dimensional coupled flow and heat transfer numerical model for the target choke valve is constructed via the FLUENT solver. Flow parameters under diverse pressure difference conditions are measured, validating the accuracy and feasibility of the established numerical model. Corresponding model hypothesis criteria and boundary condition configuration schemes are explicitly defined. Spatial distribution characteristics of the internal temperature, velocity, and pressure fields of the choke valve under different operating conditions are obtained through numerical simulation. Ten monitoring nodes uniformly arranged along the fluid domain from the inlet to the outlet are selected for quantitative analysis. The research results clarify that lower seawater temperature intensifies heat dissipation, leading to the observed temperature decrement, and confirm that the cage orifice structure dominates the flow acceleration, with the pressure drop magnitude linearly correlating with the inlet–outlet differential pressure. The research methodology and numerical findings of this study can provide a reliable basis for structural optimization and operating condition matching of cage-type choke valves applied in subsea oil and gas production systems.

Corrigendum to “The impact of filament winding configurations on the ultimate load-bearing capacity of non-metallic flexible pipes”[Ocean Eng. 341 (2025)] - Yingying Wang; Yangdong Hu; Kai Zhang; Weizheng An; Hanchen Zhou; Zeqing Lin; Segen Farid Estefen (Ocean Engineering, 2026)

The impact of filament winding configurations on the ultimate load-bearing capacity of non-metallic flexible pipes - Yingying Wang; Yangdong Hu; Kai Zhang; Weizheng An; Hanchen Zhou; Zeqing Lin; Segen Farid Estefen (Ocean Engineering, 2025)

Theoretical and numerical methods for predicting the structural stiffness of unbonded flexible riser for deep-sea mining under axial tension and internal pressure - Haibo Sun; Yingying Wang; Lusheng Jia; Zeqing Lin; Hao Yu (Ocean Engineering, 2024)

Effects of urbanization on increasing heat risks in South China - Haoyu Ye; Zeqing Huang; Luliang Huang; Lijie Lin; Ming Luo (International Journal of Climatology, 2018)
This study examines the spatio‐temporal changes of heat risk in South China and the possible effects of urbanization using a dynamic method for classifying urban and rural sites based on time‐varying DMSP‐OLS night‐time light images. Ten different indicators are analysed, which include daily means and consecutive heat wave (HW) measures at 86 stations in Guangdong Province from 1971 to 2014. Results show that these heat risk indicators have been intensifying across the study area, and the intensifying trends are more profound in urbanized and populated areas (e.g., the Pearl River Delta) than less urbanized inland areas. In addition, the mean of daily maximum, minimum, and mean temperatures in urban (rural) areas increased by 0.35 (0.24), 0.21 (0.11), and 0.23 (0.13) °C per decade, and urbanization contributes to 31, 48, and 43% of the total trends, respectively. We also estimate that the urbanization effects on (contributions to) the increasing hot days and warm nights are 2.52 (36%) and 4.21 days per decade (53%). Moreover, urbanization induces an additional increase in the frequency and participating days of HW by 0.44 events (49%) and 3.96 days (51%) per decade, respectively.

Nickle(II) ions exacerbate bleomycin-induced pulmonary inflammation and fibrosis by activating the ROS/Akt signaling pathway - Lawei Yang; Ziying Lin; Yahong Wang; Chunyan Li; Wenya Xu; Qinglan Li; Weimin Yao; Zeqing Song; Gang Liu (Environmental Science and Pollution Research, 2018)